The use of blood-flow restriction to enhance high-intensity endurance performance and skeletal muscle adaptation - Mitchell, E. (University Loughborough, 2019)
Post-exercise blood flow restriction (BFR) is a novel training method which, through alterations to the haemodynamic, metabolic and hypoxic stimulus, could augment skeletal muscle adaptation in endurance trained individuals. The studies described in this thesis investigated the combined effect of post-exercise BFR and interval training on angiogenic and mitochondrial biogenic molecular and adaptive responses and high-intensity endurance performance. It was initially demonstrated that a very strong correlation exists between critical power (CP), an important parameter of endurance performance, and indices of skeletal muscle capillarity (r = 0.94), implying that skeletal muscle capillarity is an important determinant of CP (Chapter 3). Chapter 4 investigated the efficacy of combining post-exercise BFR with 4 weeks of sprint interval training (SIT) (4-7 x 30 s maximal bouts) in trained individuals. SIT increased CP by ~3.5% in trained individuals, but the addition of BFR did not enhance this further. In contrast, neither skeletal muscle capillarity or mitochondrial protein content increased following SIT with or without BFR. However, there was a trend (P = 0.06) for an increase in proliferating endothelial cells after four weeks of SIT only with post-exercise BFR, tentatively suggesting that post-exercise BFR could elicit an enhanced angiogenic response when undertaken with a greater training duration and/or volume. This was investigated in Chapter 6 in which the time course of transient transcriptional changes during two weeks of post-exercise BFR combined with a higher volume high intensity interval training (HIIT) modality was examined. BFR did not enhance the transient increases in VEGF, PGC-1a of HIF-1a mRNA following HIIT during two-weeks of training and did not increase VEGF protein content. There was however, an increase in resting eNOS mRNA after two weeks only when HIIT was combined with post-exercise BFR, suggesting BFR elicited an increased shear stress stimulus. There was no increase in mitochondrial protein content or citrate synthase activity following 2 weeks of HIIT with or without post-exercise BFR. Collectively the findings from these studies imply that post-exercise BFR does not increase mitochondrial content, but although there was no increase in skeletal muscle capillarity, there were suggestions that post-exercise BFR could elicit an enhanced angiogenic stimulus when undertaken with higher training volumes and could subsequently increase performance.